Analysis of regional government financial performance and impact on welfare society - Nur Nida Karimah; Sarwani Sarwani; Ade Adriani (Faculty of Economics and Business Mulawarman University, 2020)
This study aims to determine and analyze the influence of local government financial performance consisting of variables of regional independence, effectiveness of regional finances, regional revenue growth, and the suitability of regional spending on welfare society. The study was conducted in 13 regencies/cities in South Kalimantan Province using secondary data from 2013-2017. The study was conducted using 65 data, which were analyzed using multiple linear regression analysis. The results of the study provide empirical evidence that only the regional independence variable has a significant influence on the welfare society in all regencies/cities in South Kalimantan Province.